INTEGRATION OF SCOUTING VALUES IN THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT FOR STRENGTHENING ELEMENTARY SCHOOL STUDENTS' CHARACTER - Aggasi , Andi; Joko Sutarto; Tri Suminar (Antis Publisher, 2025)
Objective : This development research aims to determine the Integration of Scouting Values in the Pancasila Student Profile Strengthening Project for Strengthening Elementary School Students' Character. Method : The research in this study uses the Research and Development (R&D) method of the Thiagarajan model. The Development Research was conducted by taking samples in this study were 30 students in class VA and VB each during the initial needs and 20 students in the product feasibility test. Data collection techniques were carried out using interviews and observations. Results : From the validation results of 3 people, the guidebook received an assessment above 50%. Validator I with a validation result of 100%, which means that the product developed obtained a very valid value and can be used without revision. Validator II with a validation of 80% is very valid and can be used without revision. And validator III with a validation result of 97.5% is very valid and can be used without revision. The conclusion is that from the three validators, the guidebook for integrating scouting values into the Pancasila student profile strengthening project is suitable for use without revision. While the control class without using the guidebook for integrating scouting values into the Pancasila student profile project with an average of 0.7231, which means the high and ineffective category. From the results of the implementation of the integration activities of the scouting values into the Pancasila student profile project which were effectively implemented at SD Negeri 2 Lemahabang, the researcher disseminated this guidebook using the dissemination technique through the Lemahabang KKG Gugus which was attended by 1 representative from each school. Novelty : The researcher developed a guidebook for Integrating Scouting Values in the Pancasila Student Profile Strengthening Project.